Transformasi Teknologi Blokchain Dalam Sistem Keuangan Syariah Pada Bank Syariah Indonesia KC Msakassar Sulawesi Selatan (Perspektif Fikih Muamalat) - Muhajir, Ahmad; Lutfi, Mukhtar; M, Misbahuddin; Haddade, Abdul Wahid; Syatar, Abd (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the transformation of blockchain technology within the Islamic financial system at Bank Syariah Indonesia, Makassar Branch, South Sulawesi (from the perspective of fiqh muamalat). The specific objectives of this research are: 1) To analyze the presence and application of blockchain technology in Indonesia's Islamic financial system. 2) To explore the perspective of Fiqh Muamalat regarding the feasibility of utilizing blockchain technology in the Islamic financial system. 3) To identify opportunities and challenges in implementing blockchain technology within the Islamic financial sector. This research employs a qualitative method with a descriptive approach. The findings indicate that: 1) Blockchain has the potential to enhance efficiency, transparency, and reliability in financial systems; however, its implementation in the Islamic sector is hindered by unclear regulations and the necessity to adhere to Sharia principles. 2) The perspective of fiqh muamalat at Bank Syariah Indonesia Makassar recognizes blockchain's potential to support Islamic finance, provided it is designed in compliance with Sharia values. 3) Blockchain technology offers opportunities such as increased transparency, efficiency, financial inclusion, and innovation in Islamic financial products, while its challenges include regulatory readiness, infrastructure development, resistance to change, and data security and privacy.